2016
DOI: 10.1186/s13256-016-0825-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis presenting with atypical hemolytic uremic syndrome associated with a variant of complement factor B in an adult: a case report

Abstract: BackgroundNon-Shiga toxin-associated hemolytic uremic syndrome is known to be caused by dysregulation of the alternative complement pathway. Infections, drugs, pregnancy, bone marrow transplantation, malignancy, and autoimmune disorders have all been reported to trigger episodes of atypical hemolytic uremic syndrome. To the best of our knowledge, there have been no previous reports of an association between diabetic ketoacidosis and atypical hemolytic uremic syndrome.Case presentationWe describe a case of a 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were diagnosed as systemic lupus erythematosus and Evans syndrome and accompanied by thrombocytopenia (7). In addition, a few cases with a combination of atypical hemolytic syndrome and diabetic ketoacidosis have been described in the literature (8,9). In this case, as shown in Table 1, thrombocytopenia was not observed in the clinical follow-up.…”
Section: Rhabdomyolysis and Kidney Damage Are Seen In Patients Who Armentioning
confidence: 63%
“…After managing DKA and TTP simultaneously, his condition improved with the resolution of both TTP and DKA. Zhu et al highlighted a case of a diabetic patient who presented with DKA and typical manifestations of microangiopathy suggestive of TMA [ 6 ]. Another case report presented a case of DKA-induced TTP in a young patient.…”
Section: Discussionmentioning
confidence: 99%